Direito e autoritarismo: o Supremo Tribunal Federal e os processos de habeas-corpus entre 1964-1969 - Santos, Fabricia Cristina de Sá (2008)
The main goal of this work is to examine the position of the Supreme Court (STF) regarding habeas-corpus requests during the first years of the Military Regime in Brazil (1964-1969). The principal question that we tried to answer was, in the face of the gradual installation of authoritarianism and the suspension of the Right of the State, beginning with the Coup of 1964, how the ministers, whose constitutional duty was to guarantee the protection of civil rights under the aegis of the Brazilian Judiciary, were able to position themselves and vote. Also, whether the voting of the STF ministers in such processes, would follow standards from such different factors regarding the means of recommendation and nomination of judges for the STF; their different professional background, public careers and political paths of those ministers prior to their placement on the Supreme Court. In order to respond to these questions, the study adopted the following processes: raising and analyzing the bibliographical material in the fields of Law and Political Science, related to the period and to the institution of habeas-corpus; quantitative and qualitative analysis of 238 processes of habeas-corpus which had been brought to the STF between 1964 and 1969, and the examination of biographical data in the professional and public areas of the ministers who composed the Supreme Court during the period in question. The data collected received statistical treatment and, with a base of career models developed, starting from the biographical information of the ministers, we could verify the weight of the political factors and the importance of the professional paths in explaining the bases of the votes issued by the ministers. The results allowed us to conclude that there was a great weight from external factors on the votes of the ministers changes in the judicial structure, internal factors weight of the vote by the court recorder, and on the career path (magistrate or politician). Research results showed that the Supreme Court (STF) adopted an intermediate posture, given the fact that there was no direct and open confrontation with the government. The court justices made an effort to use available judicial openings to grant the largest possible number of habeas corpus. However, as institutional acts and decrees were closing around the authoritarian circle, the court had its performance possibilities reduced until 1969 when the military suspended the writ of habeas corpus itself